(untitled) (Quaestiones Disputatae: temas en debate, 2021)
The objective of this article is to analyze the life stories of the university students victims of the amed conflict assigned to the physical education, recreation and sports of a private university of the department of Boyacá. For this purpose, the life stories of each university student will be analyzed, rescuing the memory of the event from the modalities of the armed conlfict in Colombia. The conclusion aim to give a broader view of what happened with the victims as a mechanism to raise awareness of the conflict through a critical stance on the effects that the armed war in the country left on this particular population.